Representasi Motivasi dan Perjuangan Hidup Generasi-Z dalam Lirik Lagu Shxtty Game Karya Day6: Analisis Semiotika Roland Barthes - Shendy Aulia Satriadi; Safiani A. Faaroek; Endang Roh Suciati; Fajarina . (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This research is a descriptive qualitative study using a constructivist paradigm, which aims to determine how the process of signification in the song lyrics “Shxtty Game” by Day6 constructs the meaning of motivation and represents the struggles of Generation Z through Roland Barthes’ semiotic analysis. This study was conducted because the song “Shxtty Game” is considered to reflect the psychological reality of young people who live under social pressure, demands for success, and emotional exhaustion in facing modern life. Data were collected through documentation, observation, and contextual analysis of the song lyrics. The analysis employed Roland Barthes’ semiotic theory, which emphasizes the process of meaning-making through three levels: denotation, connotation, and myth. The object of this study is the entire lyrics of “Shxtty Game” by Day6, with each verse analyzed to uncover the symbolic and ideological meanings contained within. The results show that “Shxtty Game” portrays life as an endless game that represents the human struggle to survive amid life’s pressures. Overall, the song “Shxtty Game” by Day6 represents the social and emotional realities of Generation Z, in which the struggle to persevere, seek life’s meaning, and remain optimistic becomes a symbol of modern human motivation in the midst of a dynamic life.